PENGARUH MOTIVASI BELAJAR TERHADAP POTENSI AKADEMIK SISWA KELAS II PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SDIT ALBASHIIRAH KARAWANG - Rafani Prima, Adya; Rifqiyyah, Hanna; Mujahidah, Khonsa; Fauziya, Nur; Jamilah, Nur (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the influence of learning motivation on the academic potential of second-grade students in Islamic Religious Education (PAI) at SDIT Albashiirah Karawang. The research employed a quantitative correlational method involving 30 students selected through total sampling. Data were collected using a Likert-scale motivation questionnaire and analyzed through correlation tests. The results show that students with higher learning motivation tend to achieve better academic outcomes in Islamic Religious Education. These findings highlight the importance of learning motivation as a key factor in enhancing students’ academic potential in integrated Islamic elementary schools.